Director's report of research in Kansas 2003 - Kansas State University. Agricultural Experiment Station (Kansas Agricultural Experiment Station Research Reports, 2004)
This report contains the title, author, and publication information for manuscripts published by station scientists. It also contains a list of the research projects that were active during that period and a financial statement for the fiscal year.
Keywords: Kansas; Agricultural Experiment Station; Research; Publications; Finances; Projects